Sociální pozice romského žáka v prestižní základní škole - Vorlíček, Radek (Lidé města, 2017)
This article focuses on the social position of Roma pupils at Prestige Elementary School, whose pupil population is predominantly homogeneous in terms of ethnicity and class. Special attention is paid to the boundary constructions within the groups of children. Drawn from an ethnographic study, data shows that in the school classroom, there is a strong feeling of dislike among the pupils of different ethnic groups. In addition, the article implicitly points out the factors that influence the ethnic and membership identity of Roma pupils within the particular context of Prestige School. To some degree, the text also offers new insight into the limits of the school success of Roma children.